Progressive und rezessive Entwicklungstendenzen norwegischer Agrarlandschaften - Gläßer, Ewald (ERDKUNDE, 1970)
The settlement and agricultural conditions of southern Norway (i. e. primarily Vest-, Sör-, and Ostlandet and Trondelag) are considered on the basis of natural or similarly defined agricultural regions (c. f. Map 2). In general the agricultural landscapes of Norway demonstrate contrasts in physiographic conditions and in current settlement and economic structure on a scale hardly known in central and west European areas. Efficient and modern agricultural areas are often directly juxtaposed with areas whose rural settlement and economy show clear tendencies to stagnation and regression. The lowland areas around the Oslo Fjord and Trondheim Fjord belong to the first type as does the coastal region of Jaeren, in south west Norway, which must at the moment be regarded as Nor way’s most intensively used agricultural landscape, particularly for dairy cattle. A number of coastal and island districts must be added to this category where intensive cultivation occurs under glass (primarily production of tomatoes and cucumbers). In addition, partial inclusion is warranted of the climatically favoured inner fjord regions in southern Norway where the commercial fruit production is unique for such a latitude. On the other hand, strong regressive development tendencies in agriculture are evident on the inner fjell, as well as on at least the upper sections of the old peasant valleys. The once characteristic ’alm’ ans ’seater’ economy of this area has suffered an especially severe reverse. There has, however, in recent years been a significant increase in another form of long range grazing, namely sheep transhumance mainly from the southern Vestlandet to the eastern fjell grazing areas.